Application of Audio-Visual Learning Media in Increasing Islamic Boarding School Students’ Tajweed Learning Outcomes - Abdul Hamid; Muhammad Khairuddin Lim Abdullah; Sitti Jamilah Amin; Abdul Halik; Ahdar Ahdar (Madrasah Tsanawiyah DDI Cilellang, 2025)
Generally, learning Tajweed in Islamic boarding schools still uses the rote method so the Tajweed material seems difficult and boring. This research aims to (1) describe the application of audio-visual learning media in Tajweed learning, (2) describe the increase in students' Tajweed learning outcomes, and (3) test the effect of applying audio-visual learning media on improving students' Tajweed learning outcomes. This study used experimental research with a quasi-experimental design. The object of this research consists of two classes, namely the experimental class and the control class. The research object was chosen purposively from two classes at the Salafiyah Marhalah Ulya, Tahfidzul Qur'an As'adiyah Wonomulyo Islamic Boarding School. The experimental class was given treatment using audio-visual media, while the control class continued to use the textbook-based lecturing method. Data was collected using observation, tests, interviews, and documentation. The data analysis technique uses a gain test. The research results show that the application of audio-visual media has an effect on increasing students' Tajweed learning outcomes. This research has implications for the importance of innovative and creative efforts by Islamic education teachers in creating audiovisual media for learning the Quran to welcome 21st-century education.